Creation of Hollow-Gaussian Beam for Optical Trap by Dual-beam Nonliear Fabry-perot Interferometer - Nguyen, Manh Thang; Ho, Quang Quy (Communications in Physics, 2021)
In this paper, a model of dual-beam nonlinear Fabry-Perot interferometer (DBNFPI) for creation laser hollow-Gaussian beam (HGB) is investigated. It includes a thin film of organic dye sandwiched between two optical mirrors, and irradiated by two signal and pump laser Gaussian beams. Based on the equation describing the output-input relation of intensities concerning pump intensity and the expression of the spatial intensity distribution of output signal beam (OSB), the range of pump intensity and collection of designed parameters are numerically calculated and discussed for HGB creation. These results give us the opportunity to use DBNFPI for optical trap of low-index dielectric particles.